PERENCANAAN JARINGAN TRANSPORT DENSE WAVELENGTH DIVISION MULTIPLEXING (DWDM) MENGGUNAKAN APLIKASI CISCO PACKET TRACER - Dhabit Fauzan; Saralina, Maya; Zira Rizqianti; Didik Aribowo (Lembaga Pengembangan Kinerja Dosen, 2023)
Communication and information technology plays a very important role in various activities. Data communication which is part of a technological development, provides enormous benefits great for its users to expedite activities. For example in activities shipping goods using sea transportation which integrates various components for the shipping process, has used data communication models both offline and online. Based on the data communication flow, one of which includes transmission, namely Dense Wavelength Division Multiplexing (DWDM) which is a network that is transmit by a single optical fiber in order to keep growing which serves to load several waves in various sizes. This article is made to find out more regarding DWDM, as well as understanding DWDM simulations using applications as planning from the DWDM network. The method used is to make a plan using Cisco Packet Tracer application, which is then analyzed from the results of reading the literature based on journals and books.